Effect of hemp protein on the physicochemical properties and flavor components of plant-based yogurt. (30th December 2022) - Xu, Jiaxin; Xu, Xinyue; Yuan, Zhiheng; Hua, Dong; Yan, Yaxin; Bai, Miao; Song, Hong; Yang, Lina; Zhu, Danshi; Liu, Jun; Huo, Dafei; Liu, He
Abstract: The aim of this study was to develop a new formulation of soybean and hemp protein fermented yogurt (SHY) and to evaluate the effects of hemp protein concentration on the physicochemical and flavor properties of yogurts. The results indicated that hemp protein rapidly reduced the pH, and increased total titratable acidity of yogurts due to the propagation of lactic acid bacteria. Stronger influence on the parameters was detected at higher hemp protein concentration. Yogurt with hemp protein has the potential to reduce the whey precipitation and improve texture and rheology compared to those of control yogurt. The key volatile components, including alcohols, esters, alkanes, and aldehydes, may be conducive to the flavor optimization of SHYs. The results of physicochemical properties and flavor substance selection also supported the high liking scores of 10% SHY in sensory evaluation. These findings demonstrated that hemp protein has great development potency as a nutritional source to produce functional dairy products with optimum quality. Highlights: The best quality of plant-based yogurt was optimized with 10% hemp protein. 10% hemp protein improved the physicochemical properties of yogurts. Hemp protein compensated for the key volatile components in yogurts. Yogurts with 10% hemp protein addition presented a great preference at sensory level.